The CetuxIMAX protocol: a non-interventional, uncontrolled, and non-comparative multicentric study for exploring the pharmacokinetics/pharmacodynamics relationships of cetuximab in head and neck cancer patients - Marin, Clemence; Ciccolini, Joseph; Lacarelle, Bruno; Auquier, Pascal; Salas, Sebastien (International Journal of Clinical Trials, 2023)
Background: In a previous pilot-study, a link between Cetuximab exposure levels (i.e., trough levels above 34 mg/ml) and clinical outcome in head and neck cancer patients was found. Considering the high inter-individual variability in Cetuximab plasma levels, lack of efficacy could thus be linked to inadequate exposure levels, rather than issues with signalling pathways at the tumor level. Methods: The CetuxIMAX study is a non-interventional, uncontrolled, and non-comparative multicentric study in patients with recurrent or metastatic head and neck squamous cell carcinoma, and treated by any Cetuximab-based regimen. A total of 122 patients will be enrolled in this study. The primary endpoint is the estimation of receiver operating characteristic (ROC) and area under the ROC curve (AUROC) of Cetuximab trough plasma level for the disease control rate (DCR). Pharmacokinetics samples will be collected at first cycle, when steady-state is reached, and during maintenance phase to monitor the Cetuximab levels throughout time. Standard PK modelling using population-approach will be performed to identify individual PK parameters and enable further simulations of exposure levels throughout the different cycles. Univariate and multivariable statistical analysis aiming at exploring any association between Cetuximab exposure levels and clinical outcome will be performed. Conclusions: Should the target therapeutic window associated with efficacy be confirmed with Cetuximab in head/neck cancer patients, this could pave the way for PK-guided dosing next. Based upon single point PK sampling, pop-PK modelling could help personalizing dosing or scheduling, to ensure an optimal toxicity-efficacy ratio with Cetuximab. Trial Registration: Trial registration number is NCT 04218136.